DETERMINANTS OF COMPANY PERFORMANCE: EVIDENCE FROM PUBLICLY LISTED PHARMACEUTICAL COMPANIES IN INDONESIA - Zaelani, Fazri
Indonesia has a large population, which is dominated by the productive age group, reaches 72%, making Indonesia has great potential in the economy both in terms of production and consumption. One of the potential industrial sectors in Indonesia is the pharmaceutical industry sector. From the supply side, the government supports it through foreign investment policies that can reach one hundred percent. In addition, Indonesia is also rich in medicinal raw materials. From the demand side, the government is promoting the National Health Insurance (JKN) program. In addition, the potential for consumption of pharmaceutical products accelerated by the impact of the pandemic is even greater. The potential for the pharmaceutical industry is very large in Indonesia. However, there are many pharmaceutical companies whose performance continues to decline. Therefore, it is important to know the determinant factors that affect company performance in the pharmaceutical industry in Indonesia. So that companies can formulate more appropriate policy directions and strategies to improve company performance amid this enormous potential and momentum. In this study, we will explore the determinants that affect the performance of pharmaceutical companies registered publicly in Indonesia during the period 2015 - 2019. Company performance is reflected in the value of Return on Assets (ROA) and the determination factor consists of factors that can be directed by management, namely company size, level of liquidity, level of leverage, company growth, and level of tangibility. By using multiple regression panel data with the Fixed Effect Model (FEM), the result shows that size has a significant negative effect on company performance. Meanwhile, leverage and growth have a significant positive effect on company performance. However, liquidity and tangibility do not have a significant effect on company performance.